2020
DOI: 10.1186/s12887-020-02313-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, prenatal diagnosis, and neonatal outcomes of congenital heart defects in eastern China: a hospital-based multicenter study

Abstract: Background: Congenital heart defect is the leading malformation in China. There may have been changes in congenital heart defect incidence because of birth policy shift in China over past years. This study aimed to investigate the epidemiology, prenatal diagnosis, and outcomes of congenital heart disease to improve medical and policy decisions. Methods: Data on cases of congenital heart disease identified during 2014-2018 were taken from the Zhejiang provincial birth defects surveillance system. Chi-square tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
5
27
1
2
Order By: Relevance
“…We have screened a large population of term babies using POS and have demonstrated its efficacy as well as feasibility. CCHD has a reported incidence of 1.6 to 1.7 per 1000 births 15,16 , which is comparable to our findings. Furthermore, positive predictive value and false positive rates are comparable to statistics reported in other studies 9,10 .…”
Section: Discussionsupporting
confidence: 92%
“…We have screened a large population of term babies using POS and have demonstrated its efficacy as well as feasibility. CCHD has a reported incidence of 1.6 to 1.7 per 1000 births 15,16 , which is comparable to our findings. Furthermore, positive predictive value and false positive rates are comparable to statistics reported in other studies 9,10 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we monitored a large sample of pregnant women in the city of Beijing for 3 years to reflect the status of CHD in this population. The incidence of total CHD increased from 10.29‰ in 2018 to 13.45‰ in 2020 and was slightly higher than the global level, i.e., 8-10 ‰ (10); however, the rate of CHD was much lower than that in other studies in China, such as in Zhejiang Province (20.57‰) in 2018 (11). The increasing trend is consistent with most previous reports in China (6) and other countries (10).…”
Section: Discussionsupporting
confidence: 85%
“…However, data concerning the effect of a younger maternal age on CHD are limited, and the age classification standard also differed. Our age division is consistent with a previously published study investigating a population from Zhejiang Province (11), but the result is inconsistent, the reason may be related to the small sample size of CHD/CCHD in younger pregnant women. Therefore, we should focus on older pregnant women as well as the younger pregnant women.…”
Section: Discussionsupporting
confidence: 85%
“…A study from China showed that fetal echocardiography had a high sensitivity and specificity for detecting major CHDs and had satisfactory positive and negative likelihood ratios in both the low-risk (88.2% and 100%, respectively) and high-risk (100% and 99.9%, respectively) populations [8]. However, 74.4%-88.9% of the prenatally diagnosed CHD cases were terminated [8,9]. To reduce the high abortion rate and to improve the therapeutic outcomes of CCHD, we started the "prenatal diagnosis and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the promotion of prenatally diagnosed technology and improvement of government policy, the prenatal diagnosis rate of CCHD has increased during the past 2 decades in China, and there has been a high detection rate for major CHD in both low-and high-risk populations [8,9]. Pediatrics and fetal cardiologists understand well the pathophysiology and natural history of congenital heart disease in the developed countries.…”
Section: Introductionmentioning
confidence: 99%